Child Sex Tourism Recruitment Techniques - Yahya Muhammed Bah; Myrtati Dyah Artaria (Journal of Educational, Health and Community Psychology, 2020)
Â The tourism industry generates billions of dollars. However, it has negative impacts on communities. The rationale for this systematic literature review is to examine the techniques perpetrators use to recruit children into the child sex tourism, share knowledge to spark and inspire processes that will usher rapid growth from all directions in the fight against the menace. A systematic review of the literatures using different sources was actuated. Google Search Engine and Scholar Search Engine were used to search articles. In summary, the techniques used to recruit children into child sex tourism are numerous can be simply pooled and catalogued into debt bonded technique, emotional abuse technique, physical support technique, counterfeit love technique, drug addiction technique, physical abuse technique, gifts and favors technique, power and authority technique; and fake promises and special attention grooming technique.Â